Neoliberal Kültür Endüstrisi Dolayımında Neoliberal Birikim Rejimi ve Neoliberal Öznenin İmâli: Kişisel Gelişim ve Kurumsal Esenlik. - Coşkun, Berkay (Felsefelogos, 2026)
Neoliberalism is, in essence, a set of political-economic arrangements marked by privatization, the restructuring of the state in favor of capital, and the outsourcing of social responsibilities to the market and market actors. Although neoliberalism is fundamentally a political-economic order, it cannot be reduced to that order alone, since its effects have broadly permeated social life. Building on this claim, a substantial literature--through concepts such as the production of the neoliberal subject, the entrepreneurial self, human capital, and psychopolitics--argues that under neoliberalism the self is governed as if it were an enterprise, transformed into an object of investment, and shaped by neoliberal market rationality. While endorsing these insights, I argue that a disconnection persists between political-economy accounts of neoliberalism and analyses of its socio-psychological outcomes, even though these two dimensions are not mutually exclusive. Political-economy studies often address the socio-psychological dimension only marginally, whereas studies of neoliberal subjectivity frequently fail to clarify, at the level of concrete operation, how such subject formation relates to neoliberal accumulation strategies. This article aims to make that relationship explicit. I argue that the conceptualization capable of forging this link is the neoliberal culture industry. By mobilizing this concept, the article shows how the production of the neoliberal subject is connected to neoliberalism's political economy through the rise of self-help and corporate well-being.